Interlocked Dual‐Network and Superelastic Electrospun Fibrous Sponges for Efficient Low‐Frequency Noise Absorption. Issue 2 (14th August 2020) - Zong, Dingding; Cao, Leitao; Li, Yuyao; Yin, Xia; Si, Yang; Yu, Jianyong; Ding, Bin
Abstract : Traffic noise is a major source of urban noise pollution, with severe threats to the physiological and psychological health of humans. Fibrous sound absorption materials are extensively applied in the control of traffic noise pollution; however, the larger fiber diameters and monotonous internal structure of such materials result in poor low‐frequency sound‐absorbing properties or unsatisfied mechanical properties. Herein, a biomimetic and robust strategy to design ultrastrong and superelastic fibrous sound absorption sponges is reported, which is achieved by integrating a one‐step forming technique of interlocked micro/nano dual fiber networks and an in situ crosslinking approach. The obtained vine‐like interlocked structured fibrous sponges can withstand a tensile force 10 000 times their weight without deformation. Furthermore, the materials also show outstanding compression fatigue resistance and a lightweight feature (8.70 mg cm −3 ). Most importantly, the interlocked dual‐network‐induced stable fluffy‐stacked structure endows the fibrous sponges with an enhanced low‐frequency sound‐absorbing property (absorption coefficient of 0.93 at 1000 Hz), which is superior to those of commercial and reported sound absorption materials. In addition, the materials also possess good hydrophobicity and temperature resistance. This work opens new pathways for the further development of highly efficient sound‐absorbing materials. Abstract : An interlocked dual‐network‐structured polysulfone (PSU)/poly(vinylidene fluoride) (PVDF) fibrous sponge (PFFS) is successfully constructed. The fibrous sponge can withstand a tensile force 10 000 times its weight without deformation and also shows outstanding compressive fatigue resistance. Particularly, the material exhibits an enhanced low‐frequency sound‐absorbing property (absorption coefficient of 0.93 at 1000 Hz).